PENGARUH BEBERAPA BAHAN BAKU TERHADAP KARAKTERISTIK FISIKOKIMIA DAN SENSORI RENGGINANG SINGKONG (Manihot utilissima Pohl) - Hadi Munarko; Sugiyono Sugiyono (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2019)
Cassava rengginang is a traditional food having similar shape to rice rengginang but is made from cassava. The objective of this research was to know the effects of raw material on the physical and senso-ry characteristics of cassava rengginang. This research was divided into two steps. The first step was raw material preparation i.e. grated cassava, cassava flour, and a mixture of tapioca and “asian” flour 3:1 (w:w). The second step was the production of the cassava rengginang from the three raw materials. The results showed that the raw material affected the physical characteristics of cassava rengginang. Renggi-nang made from grated cassava had the lowest expansion ratio and crispness, i.e. 142.94% and 474.12 gf respectively. Rengginang made from cassava flour had higher expansion ratio and crispness (191.39% and 343.81 gf respectively), the lowest lightness (L= 71.4) and the highest brownish color (a=5.18; b=27.49). Rengginang from a mixture of tapioca and “asian” flour (3:1) had the highest crispness (244.63 gf), expansion ratio (223.95%), lightness (L=79.62), and white color (a=0.63 and b= 16.3). The differences on the physical characteristics of rengginang did not affect the sensory acceptance of the product for all attributes. Fried rengginang made from a mixture of tapioca and “asian” flour was chosen for proximate analysis because it had the highest expansion ratio, crispness and lightness among the other formula although it was not significantly different at 95% level on panelist acceptance.